Narrar la Guerra de Malvinas desde el teatro: la dramaturgia lírica de Soledad González - Maximiliano Ignacio de la Puente (IdeAs, 2023)
This paper is a study of a play by the Argentinian playwright and director Soledad González, from the province of Córdoba. The focus will be on Malvinas 74 días/1982 (2016). In this play, Argentina's dictatorial past is brought into play: the work deals with the effects of the Malvinas War, the military confrontation that took place in 1982 with the United Kingdom, with the dispute over the sovereignty of the Malvinas, Georgias, and the South Sandwich Islands. In the elaboration of this event belonging to the traumatic recent past of the country, Soledad González adopts strategies that come from post-dramatic and performative theatricalities. The analysis on the play is based on the concepts of archive and repertory (Taylor D., 2012), epidramas (González S., 2016a), a notion developed by the author herself, and performative memories (de la Puente M., 2019), among others. We argue that Malvinas 74 días/1982 constitutes an interesting example of contemporary dramatic textualities, insofar as its poetics is located at the crossroads between poetry, music, and theater. In this way, it manages to bring into play personal and collective, private and public memories of the Malvinas War, exploding and multiplying the forms and meanings associated with this event in the country's traumatic past.